Komparasi Kualitas Informasi Akuntansi dan Strategi Bertahan UMKM di Masa Pandemi - Wildatul Muawanah; Sri Trisnaningsih (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
This article aims to explore the impact of the global epidemic of Coronavirus Disease 2019 (COVID-19) for Small and Medium Enterprises (SME) in Indonesia and Malaysia using social dynamic theory, in order to add insight into the handling carried out by each of them. Each of these countries is facing a crisis during the COVID-19 pandemic and seeing how Covid-19 affects accounting practices which have implications for the quality of accounting information. SME are one of the sectors with a major contribution to a developing country such as Indonesia and Malaysia. This research is a literature review study, which uses data from previous research articles in the Mendeley database. A total of 13 articles were reviewed using the keywords, “survival strategy”, “quality of accounting information”, “SME”, “covid-19”, “Indonesia”, “Malaysia”. From the articles reviewed, 13 articles show that there are similarities regarding SME survival strategies with digitalization and differences in government policies in funding support for SME in the two countries, as well as the impact on the quality of accounting information during the pandemic. Keywords: Survival strategy; Quality of accounting information; SME; covid-19; Indonesi; Malaysia.